(untitled) (Global Journal of Management and Business Research, 2022)
This paper examines the impact of the quality of sustainability disclosure QSD on the accuracy of analyst s earnings forecast The study uses data from 1908 firm-year observations drawn from Egypt stock exchange covering 2009 to 2018 The results show evidence indicates that QSD mitigates information asymmetry by signalling QSD and improving the accuracy of analysts forecast In addition this studydistinguishes between the quantity and the quality of sustainability disclosure and examine their relationship with the accuracy of analyst forecast The empirical results confirm that the QVD and its dimensions considered in the study framework give more realistic disclosure picture than quantity does The results from the additional analysis also confirm the main result